2022
DOI: 10.3389/fpubh.2022.1072574
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anisometropia and associated factors in Shandong school-aged children

Abstract: ObjectiveTo investigate anisometropia's prevalence and associated factors in school-aged children.MethodsA cross-sectional school-based study was conducted in Shandong Province, China, including children aged 4 to 17 from 9 schools. Anisometropia was defined as the differences between the two eyes in spherical equivalent (SE) or cylinder degree of 1.00 diopter (D) or more [SE or cylindrical (CYL) difference ≥ 1.00 D] after cycloplegic autorefraction. The Generalized Linear Model (GLM) was used to analyze the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
(24 reference statements)
3
3
1
Order By: Relevance
“…Compared with previous studies, such a high prevalence of anisometropia is rare. In fact, compared to previous studies ( 5 , 35 , 37 ), there is not much difference in the prevalence of anisometropia between 7 to 9 years of age. The sharp increase in the prevalence of anisometropia is worth noting.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Compared with previous studies, such a high prevalence of anisometropia is rare. In fact, compared to previous studies ( 5 , 35 , 37 ), there is not much difference in the prevalence of anisometropia between 7 to 9 years of age. The sharp increase in the prevalence of anisometropia is worth noting.…”
Section: Discussioncontrasting
confidence: 79%
“…In 2016, a school-based study conducted in Shandong, China ( 5 ) found that 7.0% of 6,025 school children aged 4–17 years had refractive anisometropia. In 2022, in another epidemiological survey of students 4–17 years of age in Shandong, China ( 37 ), the prevalence rose to 13.2%. In the current study, we found that the prevalence of anisometropia was relatively low in early school age children (7–9 years of age) (7.8–9.0%), but it increased to 16.0% at 10 years of age, and even to 39.0% at 19 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of hyperopia tended to decrease with age (Ptrend<0.001). These results were similar to previous studies [ 44 46 ]. In particular, the prevalence of myopia increased from 30.3% in the age group of 7−8 years to 94.3% in the age group of 19−20 years, indicating the severe need for myopia prevention and control in Chinese school-age children.…”
Section: Discussionsupporting
confidence: 94%
“…Students with hyperopia ( > + 0.5 D) were 3.437 times more likely to develop astigmatism than those with emmetropia (-0.50 D to ≤ + 0.50 D), while individuals with low myopia (-3.00 D to <-0.50 D), medium myopia (-6.00 D to ≤ -3.00 D) and high myopia (SE ≤ -6.00 D) were 1.296 times, 2.695 times and 6.391 times more likely to develop astigmatism, respectively, compared with emmetropia cases. This corroborated previous studies conducted in Yiwu, China [ 32 ] and Anyang, China [ 14 ], as well as a study conducted by the MEPEDS [ 25 ] and the US VIP multicenter study [ 6 ]. We can conclude that children with refractive errors are more likely to develop astigmatism than those without refractive errors.…”
Section: Discussionsupporting
confidence: 91%